Antimicrobial strategies for ureteral stent removal after radical cystectomy: a comparative cohort study - Maurin Helen Mangold; Jennifer Kazmierczak; Marlis Gerigk; Nicolas Carl; Luisa Vivienne Renner; Maren Juliane Wenk; Maurice Stephan Michel; Karl-Friedrich Kowalewski; Niklas Westhoff (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Gas chromatography analysis of fatty acid esters and free fatty acids for the evaluation of lipase performance in textile treatment and washing - Luís C. de Sousa; Nazanin Ansari; Roland Lottenbach; Rainer Rösch; Jan Modregger; Simona Capone; Karl-Erich Jaeger; Rebecka Molitor; Stephan Thies; Paula Vidal; Manuel Ferrer; Carla C.C.R. de Carvalho (Bioresource Technology Reports, 2026)

Changes in soil mechanical and hydraulic properties through regenerative cultivation measures in long-term and farm experiments in Germany - Carolina Bilibio; Tobias Karl David Weber; Markus Hammer-Weis; Stephan Martin Junge; Simeon Leisch-Waskoenig; Janos Wack; Wiebke Niether; Andreas Gattinger; Maria Renate Finckh; Stephan Peth (Soil and Tillage Research, 2025)

Marmorgewinnung und Schmiedetätigkeit im Frühmittelalter – Ein erster Hinweis im Steinbruchrevier Spitzelofen in Kärnten/Österreich - Stephan Karl; Daniel Modl; Susanne Strobl; Roland Haubner (BHM Berg- und Hüttenmännische Monatshefte, 2024)
Zusammenfassung Im römerzeitlichen Marmorsteinbruchrevier Spitzelofen in Kärnten wurde bei archäologischen Ausgrabungen auch Hammerschlag gefunden, der aus einer frühmittelalterlichen Brandschicht stammt. Radiokarbondatierungen dieser Schicht weisen den Befund in das 8. bzw. 9. Jahrhundert n. Chr. Im Zuge der metallurgischen Untersuchung wurde plättchenförmiger Hammerschlag festgestellt. Die Dicke der Plättchen variiert zwischen etwa 30 und 100 µm. Es kann davon ausgegangen werden, dass diese Plättchen durch Verzunderung während des Schmiedevorgangs entstanden. Weiters wurde kugelförmiger Hammerschlag beobachtet, bei dem es sich um ein Gemisch aus geschmolzenem Eisen und Schlacke handelt, das beim Hochtemperaturschmieden (> 1200 °C) vom Werkstück wegspritzt. Diese Teilchen haben einen Durchmesser von etwa 250 µm. Der archäologische Kontext, der Hammerschlag und die Radiokarbondatierungen belegen eine mit der Marmorgewinnung zusammenhängende Schmiedetätigkeit im 8. und 9. Jahrhundert n. Chr. In einer einfachen Feldschmiede wurden die durch die Benutzung stumpf gewordenen Steinbruchwerkzeuge nachgeschärft. Dieser somit indirekt gewonnene Nachweis einer frühmittelalterlichen Steingewinnung am Spitzelofen deckt sich zeitlich mit der Marmorverwendung für die frühmittelalterlichen Flechtwerksteine in Karantanien (772 bis 817/828 n. Chr.).

First measurements of wind-turbine perturbations of fair-weather electric fields - Karl D. Stephan; Richard Sonnenfeld; Analies DeGroot King; Nathan Cortez; Roberto Toledo (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

New observation and analysis of window damage as evidence for energy and power content of ball lightning - Karl D. Stephan (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Reducing plastic pollution caused by demersal fisheries - Eduardo Grimaldo; Christian W. Karl; Anja Alvestad; Anna-Maria Persson; Stephan Kubowicz; Kjell Olafsen; Hanne Hjelle Hatlebrekke; Grethe Lilleng; Ilmar Brinkhof (Marine Pollution Bulletin, 2023)

Steinmetzwerkzeuge aus dem römischen Marmorsteinbruchrevier Spitzelofen (Österreich) - Stephan Karl (BHM Berg- und Hüttenmännische Monatshefte, 2023)
Zusammenfassung Im Zuge eines archäologischen Surveys im römischen Marmorsteinbruchrevier Spitzelofen im Jahr 2021 wurden unter anderen zwei Steinmetzwerkzeuge gefunden, welche die bisherige Anzahl von über 30 Steinbruchwerkzeugen von dieser Lagerstätte erweitern. Bei den Neufunden handelt es sich um Werkzeuge für die eigentliche Steinbearbeitung, d. h. für das Zurichten der abgekeilten bzw. herausgebrochenen Steinblöcke zu Roh- bzw. Halbfertigprodukten: ein zweibahniger Hammer mit ausschwingenden Enden und ein schmaler Breitmeißel. Der Hammer (lat. malleus) kann einem Hammertyp zugewiesen werden, der als archäologisches Fundstück rar, jedoch in einigen Reliefdarstellungen, zumeist auf Grabdenkmalen, von der Zeitenwende bis zum Ende des 3. Jahrhunderts n. Chr. nachzuweisen ist. Auf diesen Grabdenkmalen erscheint dieser Hammertyp stets als Teil eines Werkzeugsets, zumeist mit Messwerkzeugen und Meißeln (lat. scalpra) kombiniert. Die dargestellten Werkzeuge kennzeichnen – in einem Fall auch durch die Grabinschrift belegt – das berufliche Umfeld des Verstorbenen als Marmorarius, als eine mit Marmor arbeitende Person, dessen Arbeitsbereich sich von der Steingewinnung bis zur Herstellung von Objekten und Bauten aus Marmor erstrecken kann. Entgegen der häufigen Annahme, dass sich Werkzeuge der Steinbearbeitung bis zur Neuzeit kaum verändert haben, zeigen sie doch charakteristische Eigenschaften ihrer Zeit.

Effect of Different Organic Amendments on Actual and Achievable Yields in a Cereal-Based Cropping System - Xavier Albano; Andrew P. Whitmore; Ruben Sakrabani; Cathy L. Thomas; Tom Sizmur; Karl Ritz; Jim Harris; Mark Pawlett; Chris Watts; Stephan M. Haefele (Journal of Soil Science and Plant Nutrition, 2023)
Soil fertility is at risk in intensive cropping systems when using an exclusive regime of inorganic fertilisers without returning sufficient organic matter to the soil. Our objective was to evaluate the long-term effects of commonly used organic amendments interacting with different rates of inorganic nitrogen fertiliser on crop yields of winter wheat. Yield data from winter wheat were collected for five seasons between 2013 and 2019 from a continuous field trial based at Rothamsted Research, SE England. Organic amendments (anaerobic digestate, compost, farmyard manure, and straw at a rate of 0 and 2.5 ton C per hectare) and five rates of inorganic nitrogen fertiliser (NH 4 NO 3 at 0, 80, 150, 190, 220 kg N ha −1 ) were applied to winter wheat grown in an arable rotation. At the same inorganic N rate, grain yields for the different organic amendment treatments (excluding the straw treatment) were statistically similar but significantly greater than the unamended control treatment. The nitrogen rate required for optimum yields tended to be lower in plots receiving a combination of organic amendments and mineral fertiliser. Based on the observed and modelled response functions, organic amendments excluding straw increased maximum achievable yields compared to non-amended controls. The size of the effect varied between seasons and amendments (+4.6 to +19.0% of the control yield), increasing the mean maximum achievable yield by 8.8% across four seasons. We conclude that the application of organic amendments can increase the yield potential in winter wheat substantially over what is achievable with inorganic fertiliser only.

Modeling the Neuruppin ball lightning incident - Karl D. Stephan (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Pro-environmental habits: An underexplored research agenda in sustainability science - Noah Linder; Matteo Giusti; Karl Samuelsson; Stephan Barthel (Ambio, 2022)
Habits are the fundamental basis for many of our daily actions and can be powerful barriers to behavioural change. Still, habits are not included in most narratives, theories, and interventions applied to sustainable behaviour. One reason societies struggle to reach policy goals and people fail to change towards more pro-environmental lifestyles might be that many behaviours are now bound by strong habits that override knowledge and intentions to act. In this perspective article, we provide three arguments for why pro-environmental habits are a needed research agenda in sustainability science: (1) habit theory highlights how behaviour is heavily reliant on automatic processes, (2) the environmental context sets boundary conditions for behaviour, shape habits, and cues action responses, and (3) our habits and past behaviour shape our values and self-identity. These arguments highlight the transformative potential of looking at sustainable behaviours through a habit lens. We believe a research agenda on pro-environmental habits could generate a more holistic understanding of sustainable behaviours and complement today’s dominating approaches which emphasize reasoned decisions and intrinsic motivations such as values, norms, and intentions to understand and predict pro-environmental behaviour. We highlight evident knowledge gaps and practical benefits of considering habit theory to promote pro-environmental behaviours, and how habit architecture could be utilized as a strong leverage point when designing, modifying, and building urban environments.

Threshold values of grass pollen (Poaceae) concentrations and increase in emergency department visits, hospital admissions, drug consumption and allergic symptoms in patients with allergic rhinitis: a systematic review - Jana Becker; Nadine Steckling-Muschack; Isabella Mittermeier; Karl-Christian Bergmann; Stephan Böse-O’Reilly; Jeroen Buters; Athanasios Damialis; Katharina Heigl; Joachim Heinrich; Michael Kabesch; Hanna Mertes; Dennis Nowak; et al. (Aerobiologia, 2021)

Correction to: Self‑reported cardiovascular health of teachers: results from the 5‑year follow‑up of the Gutenberg Health Study cohort - Merle Riechmann‑Wolf; Sylvia Jankowiak; Andreas Schulz; Janice Hegewald; Karla Romero Starke; Falk Liebers; Karin Rossnagel; Alicia Poplawski; Natalie Arnold; Matthias Nübling; Andreas Seidler; Manfred Beutel; et al. (International Archives of Occupational and Environmental Health, 2021)

A systematic review of threshold values of pollen concentrations for symptoms of allergy - Nadine Steckling-Muschack; Hanna Mertes; Isabella Mittermeier; Paul Schutzmeier; Jana Becker; Karl-Christian Bergmann; Stephan Böse-O′Reilly; Jeroen Buters; Athanasios Damialis; Joachim Heinrich; Michael Kabesch; Dennis Nowak; et al. (Aerobiologia, 2021)

Untersuchungen von Hammerschlag aus einer Schmiedeesse im römerzeitlichen Marmorsteinbruchrevier Spitzelofen in Kärnten, Österreich - Stephan Karl; Daniel Modl; Susanne Strobl; Roland Haubner (BHM Berg- und Hüttenmännische Monatshefte, 2021)
Zusammenfassung Im römerzeitlichen Marmorsteinbruchrevier Spitzelofen in Kärnten wurden bei archäologischen Ausgrabungen metallurgische Reste aus einer Schmiedeesse gefunden, die die Bearbeitung der Werkzeuge in unmittelbarer Nähe zum Steinbruch belegen. Aus einer holzkohlehaltigen Schicht wurden drei Korngrößenfraktionen von Hammerschlag gewonnen und untersucht. In allen Proben wurden die Eisenoxide Wüstit (FeO), Magnetit (Fe 3 O 4 ) und Hämatit (Fe 2 O 3 ) nachgewiesen. In der feinsten Fraktion (0–0,5 mm) befanden sich eher gleichförmige Hammerschlagpartikel neben größeren Anteilen an Kalzit (Marmor) und Quarz. In den gröberen Fraktionen lag der Hammerschlag plättchenförmig vor. In den Proben konnte neben den Eisenoxiden lokal auch Schlacke und metallisches Eisen nachgewiesen werden. Das Vorliegen von plättchenförmigem Hammerschlag zeigt, dass dieser durch Verzunderung während des Schmiedevorgangs entstanden ist und bei den verwendeten Schmiedetemperaturen die Schmelzpunkte von Gusseisen und Schlacke nicht erreicht wurden (T Für die Nachbearbeitung von groben Bergbauwerkzeugen (Doppelspitzschlägel, Setzkeile usw.) war es vermutlich nicht notwendig, das gesamte Werkzeug auf Schmiedetemperatur zu erwärmen, sondern nur so weit, dass die gewünschte Verformung erreicht werden konnte.

Untersuchung eines Doppelspitzschlägels aus dem römerzeitlichen Marmorsteinbruchrevier Spitzelofen in Kärnten, Österreich - Wolfgang Scheiblechner; Stephan Karl; Daniel Modl; Susanne Strobl; Roland Haubner (BHM Berg- und Hüttenmännische Monatshefte, 2021)
Zusammenfassung Ein Doppelspitzschlägel aus dem römerzeitlichen Marmorsteinbruchrevier Spitzelofen in Kärnten wurde untersucht, um dessen Herstellung und Einsatz bei der Marmorbearbeitung beurteilen zu können. Das Eisen wurde in Form von Luppen aus Rennfeuern erhalten. Inhomogene Kohlenstoffverteilungen im Schlägel können auf die Eisenherstellung im Rennfeuer sowie die Verarbeitung durch Schmieden zurückgeführt werden. Das Eisen des Doppelspitzschlägels besteht weitgehend aus Stahl mit eutektoidem (0,8 % C) Kohlenstoffgehalt, wobei vor allem an der Spitze ein Gradient zu fast reinem Ferrit beobachtet wurde. Es wurden die erwarteten Stahlgefüge, wie Perlit, Zwischenstufe, Widmannstättscher Ferrit und Ferrit, gefunden, jedoch kein Martensit. Um dies abzuklären, wurden Spitzen nachgeschmiedet und gehärtet, wobei auch hier kein Martensit an den Oberflächen der Spitzen nachgewiesen werden konnte. Versuche zur Marmorbearbeitung mit einem nachgeschmiedeten Doppelspitzschlägel zeigten, dass eine regelmäßige Nachbearbeitung der Werkzeuge notwendig war, was auch die im Steinbruchrevier gefundenen Schmiedeplätze erklärt.

The virus–host interface: Molecular interactions of Alphacoronavirus‐1 variants from wild and domestic hosts with mammalian aminopeptidase N - Ximena A. Olarte‐Castillo; Joana F. dos Remédios; Felix Heeger; Heribert Hofer; Stephan Karl; Alex D. Greenwood; Marion L. East (Molecular Ecology, 2021)
The Alphacoronavirus ‐ 1 species include viruses that infect numerous mammalian species. To better understand the wide host range of these viruses, better knowledge on the molecular determinants of virus–host cell entry mechanisms in wildlife hosts is essential. We investigated Alphacoronavirus ‐ 1 infection in carnivores using long‐term data on Serengeti spotted hyenas ( Crocuta crocuta ) and molecular analyses guided by the tertiary structure of the viral spike (S) attachment protein's interface with the host receptor aminopeptidase N (APN). We sequenced the complete 3′‐end region of the genome of nine variants from wild African carnivores, plus the APN gene of 15 wild carnivore species. Our results revealed two outbreaks of Alphacoronavirus ‐ 1 infection in spotted hyenas associated with genetically distinct canine coronavirus type II (CCoVII) variants. Within the receptor binding domain (RBD) of the S gene the residues that directly bind to the APN receptor were conserved in all variants studied, even those infecting phylogenetically diverse host taxa. We identified a variable region within RBD located next to a region that directly interacts with the APN receptor. Two residues within this variable region were under positive selection in hyena variants, indicating that both sites were associated with adaptation of CCoVII to spotted hyena APN. Analysis of APN sequences revealed that most residues that interact with the S protein are conserved in wild carnivores, whereas some adjacent residues are highly variable. Of the variable residues, four that are critical for virus–host binding were under positive selection and may modulate the efficiency of virus attachment to carnivore APN.

Spatial population genomics of a recent mosquito invasion - Thomas L. Schmidt; Tom Swan; Jessica Chung; Stephan Karl; Samuel Demok; Qiong Yang; Matt A Field; Mutizwa Odwell Muzari; Gerhard Ehlers; Mathew Brugh; Rodney Bellwood; Peter Horne; et al. (Molecular Ecology, 2021)
Population genomic approaches can characterize dispersal across a single generation through to many generations in the past, bridging the gap between individual movement and intergenerational gene flow. These approaches are particularly useful when investigating dispersal in recently altered systems, where they provide a way of inferring long‐distance dispersal between newly established populations and their interactions with existing populations. Human‐mediated biological invasions represent such altered systems which can be investigated with appropriate study designs and analyses. Here we apply temporally restricted sampling and a range of population genomic approaches to investigate dispersal in a 2004 invasion of Aedes albopictus (the Asian tiger mosquito) in the Torres Strait Islands (TSI) of Australia. We sampled mosquitoes from 13 TSI villages simultaneously and genotyped 373 mosquitoes at genome‐wide single nucleotide polymorphisms (SNPs): 331 from the TSI, 36 from Papua New Guinea (PNG) and four incursive mosquitoes detected in uninvaded regions. Within villages, spatial genetic structure varied substantially but overall displayed isolation by distance and a neighbourhood size of 232–577. Close kin dyads revealed recent movement between islands 31–203 km apart, and deep learning inferences showed incursive Ae. albopictus had travelled to uninvaded regions from both adjacent and nonadjacent islands. Private alleles and a co‐ancestry matrix indicated direct gene flow from PNG into nearby islands. Outlier analyses also detected four linked alleles introgressed from PNG, with the alleles surrounding 12 resistance‐associated cytochrome P450 genes. By treating dispersal as both an intergenerational process and a set of discrete events, we describe a highly interconnected invasive system.

Self-reported cardiovascular health of teachers: results from the 5-year follow-up of the Gutenberg Health Study cohort - Merle Riechmann-Wolf; Sylvia Jankowiak; Andreas Schulz; Janice Hegewald; Karla Romero Starke; Falk Liebers; Karin Rossnagel; Alicia Poplawski; Natalie Arnold; Matthias Nübling; Andreas Seidler; Manfred Beutel; et al. (International Archives of Occupational and Environmental Health, 2021)
Objectives Following an exploratory approach, we examined cardiovascular disease risk factors at baseline and the 5-year incidence proportion of self-reported doctor-diagnosed cardiovascular diseases (CVD) in teachers and other occupational groups of the Gutenberg Health Study. Methods Study participants lived in the region of Mainz, Germany. Data from 6510 working participants without prevalent CVD at baseline (2007–2012) were analyzed. Participants were teachers ( n = 215), other professionals from the health, social or educational (HSE) fields ( n = 1061) or worked outside the HSE fields ( n = 5234). For occupational comparisons, we estimated prevalence ratios (PR) for each CVD risk factor at baseline with robust Poisson regression analyses. We calculated crude CVD incidence rates based on the observed 5-year CVD cumulative incidence at follow-up and estimated age-weighted incidence proportions. All analyses were stratified by sex. Results Male non-HSE workers showed a higher prevalence of smoking and physical inactivity than male teachers (PR 2.26; 95%-CI: 1.06–4.82/PR 1.89; 95%-CI: 1.24–2.87). In contrast, non-HSE workers and other HSE professionals were less likely to have reported an unhealthy alcohol intake than teachers. Differences were attenuated after SES-adjustment. We did not detect occupational group-specific differences in CVD incidence. However, there were only two cases of CVD among the teachers. Conclusion Particularly male teachers showed a healthier lifestyle regarding physical inactivity and smoking. Nevertheless, occupational-medical care practitioners and researchers need to be aware of the relatively heightened prevalence of unhealthy alcohol intake in female and male teachers, and in absolute terms, the high hypertension prevalence in male teachers.

Myositis in Lewis rats induced by the superantigen Staphylococcal enterotoxin A - Alexander Emmer; Abimbola Abobarin-Adeagbo; Andreas Posa; Berit Jordan; Karl-Stefan Delank; Martin Sebastian Staege; Alexander Surov; Stephan Zierz; Malte Erich Kornhuber (Molecular Biology Reports, 2019)

Tree species from two contrasting habitats for use in harsh urban environments respond differently to extreme drought - Laura Myrtiá Faní Stratópoulos; Chi Zhang; Swantje Duthweiler; Karl-Heinz Häberle; Thomas Rötzer; Chao Xu; Stephan Pauleit (International Journal of Biometeorology, 2019)

Carbon monoxide elimination for health and safety: new powerful silica-based adsorbents applied in continuous breakthrough experiments at elevated laboratory scale - Karl Blender; Helena Horn; Bernd Niemeyer; Stephan Lassen (Air Quality, Atmosphere & Health, 2018)

Effect of Technically Relevant X-Ray Doses on the Structure and Function of Alcohol Dehydrogenase and Hen Egg-White Lysozyme - Lisa-Marie Schaden; Miriam Wimmer-Teubenbacher; Johannes Poms; Peter Laggner; Karl Lohner; Stephan Sacher; Johannes G. Khinast; Sharareh Salar-Behzadi (Pharmaceutical Research, 2018)

EXIOBASE 3: Developing a Time Series of Detailed Environmentally Extended Multi‐Regional Input‐Output Tables - Konstantin Stadler; Richard Wood; Tatyana Bulavskaya; Carl‐Johan Södersten; Moana Simas; Sarah Schmidt; Arkaitz Usubiaga; José Acosta‐Fernández; Jeroen Kuenen; Martin Bruckner; Stefan Giljum; Stephan Lutter; et al. (Journal of Industrial Ecology, 2018)
Summary Environmentally extended multiregional input‐output (EE MRIO) tables have emerged as a key framework to provide a comprehensive description of the global economy and analyze its effects on the environment. Of the available EE MRIO databases, EXIOBASE stands out as a database compatible with the System of Environmental‐Economic Accounting (SEEA) with a high sectorial detail matched with multiple social and environmental satellite accounts. In this paper, we present the latest developments realized with EXIOBASE 3—a time series of EE MRIO tables ranging from 1995 to 2011 for 44 countries (28 EU member plus 16 major economies) and five rest of the world regions. EXIOBASE 3 builds upon the previous versions of EXIOBASE by using rectangular supply‐use tables (SUTs) in a 163 industry by 200 products classification as the main building blocks. In order to capture structural changes, economic developments, as reported by national statistical agencies, were imposed on the available, disaggregated SUTs from EXIOBASE 2. These initial estimates were further refined by incorporating detailed data on energy, agricultural production, resource extraction, and bilateral trade. EXIOBASE 3 inherits the high level of environmental stressor detail from its precursor, with further improvement in the level of detail for resource extraction. To account for the expansion of the European Union (EU), EXIOBASE 3 was developed with the full EU28 country set (including the new member state Croatia). EXIOBASE 3 provides a unique tool for analyzing the dynamics of environmental pressures of economic activities over time.

Visualization of tumor heterogeneity by in situ padlock probe technology in colorectal cancer - Amin El-Heliebi; Karl Kashofer; Julia Fuchs; Stephan W. Jahn; Christian Viertler; Andrija Matak; Peter Sedlmayr; Gerald Hoefler (Histochemistry and Cell Biology, 2017)

Mtss1 promotes maturation and maintenance of cerebellar neurons via splice variant-specific effects - Thorsten Sistig; Fanziska Lang; Sebastian Wrobel; Stephan L. Baader; Karl Schilling; Britta Eiberger (Brain Structure and Function, 2017)

Recent Development of Thin Slab Casting and Rolling Technology in a Challenging Market - Karl Hoen; Christoph Klein; Stephan Krämer; Jea-Sook Chung (BHM Berg- und Hüttenmännische Monatshefte, 2016)

Duricrusts in soils of the Alentejo (southern Portugal)—types, distribution, genesis and time of their formation - Daniela Sauer; Christine Stein; Stephan Glatzel; Jürgen Kühn; Mehdi Zarei; Karl Stahr (Journal of Soils and Sediments, 2015)

13 C discrimination between diet, faeces, milk and milk components - Stephan Schneider; Karl Auerswald; Gerhard Bellof; Hans Schnyder (Isotopes in Environmental and Health Studies, 2015)

Environmental drivers of ectomycorrhizal communities in Europe's temperate oak forests - Laura M. Suz; Nadia Barsoum; Sue Benham; Hans‐Peter Dietrich; Karl Dieter Fetzer; Richard Fischer; Paloma García; Joachim Gehrman; Ferdinand Kristöfel; Miklós Manninger; Stefan Neagu; Manuel Nicolas; et al. (Molecular Ecology, 2014)
Ectomycorrhizal fungi are major ecological players in temperate forests, but they are rarely used in measures of forest condition because large‐scale, high‐resolution, standardized and replicated belowground data are scarce. We carried out an analysis of ectomycorrhizas at 22 intensively monitored long‐term oak plots, across nine European countries, covering complex natural and anthropogenic environmental gradients. We found that at large scales, mycorrhizal richness and evenness declined with decreasing soil pH and root density, and with increasing atmospheric nitrogen deposition. Shifts in mycorrhizas with different functional traits were detected; mycorrhizas with structures specialized for long‐distance transport related differently to most environmental variables than those without. The dominant oak‐specialist Lactarius quietus, with limited soil exploration abilities, responds positively to increasing nitrogen inputs and decreasing pH . In contrast, Tricholoma , Cortinarius and Piloderma species , with medium‐distance soil exploration abilities, show a consistently negative response. We also determined nitrogen critical loads for moderate (9.5–13.5 kg N/ha/year) and drastic (17 kg N/ha/year) changes in belowground mycorrhizal root communities in temperate oak forests. Overall, we generated the first baseline data for ectomycorrhizal fungi in the oak forests sampled, identified nitrogen pollution as one of their major drivers at large scales and revealed fungi that individually and/or in combination with others can be used as belowground indicators of environmental characteristics.

Erratum to: The molecular basis of the specificity and cross-reactivity of the NeuN epitope of the neuron-specific splicing regulator, Rbfox3 - Stephan Maxeiner; Alexander Glassmann; Hung-Teh Kao; Karl Schilling (Histochemistry and Cell Biology, 2014)

The molecular basis of the specificity and cross-reactivity of the NeuN epitope of the neuron-specific splicing regulator, Rbfox3 - Stephan Maxeiner; Alexander Glassmann; Hung-Teh Kao; Karl Schilling (Histochemistry and Cell Biology, 2014)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Flux-based ozone risk assessment for adult beech forests - Ludger Grünhage; Rainer Matyssek; Karl-Heinz Häberle; Gerhard Wieser; Ursula Metzger; Michael Leuchner; Annette Menzel; Jochen Dieler; Hans Pretzsch; Winfried Grimmeisen; Lothar Zimmermann; Stephan Raspe (Trees, 2012)

Integrated Modeling of Global Change Impacts on Agriculture and Groundwater Resources - Roland Barthel; Tim G. Reichenau; Tatjana Krimly; Stephan Dabbert; Karl Schneider; Wolfram Mauser (Water Resources Management, 2012)

Cell Death as a Regulator of Cerebellar Histogenesis and Compartmentation - Jakob Jankowski; Andreas Miething; Karl Schilling; John Oberdick; Stephan Baader (The Cerebellum, 2011)

Dau c 1.01 and Dau c 1.02-silenced transgenic carrot plants show reduced allergenicity to patients with carrot allergy - Susanna Peters; Jafargholi Imani; Vera Mahler; Kay Foetisch; Susanne Kaul; Kathrin E. Paulus; Stephan Scheurer; Stefan Vieths; Karl-Heinz Kogel (Transgenic Research, 2011)

Early occurrence of lung adenocarcinoma and breast cancer after radiotherapy of a chest wall sarcoma in a patient with a de novo germline mutation in TP53 - Alessandra Ferrarini; Agnes Auteri-Kaczmarek; Alessia Pica; Nemya Boesch; Karl Heinimann; Stephan C. Schäfer; Sara Vesnaver-Megalo; Viviane Cina; Jacques S. Beckmann; Christian Monnerat (Familial Cancer, 2011)

Proposal for a revised taxonomy of the family Filoviridae: classification, names of taxa and viruses, and virus abbreviations - Jens H. Kuhn; Stephan Becker; Hideki Ebihara; Thomas W. Geisbert; Karl M. Johnson; Yoshihiro Kawaoka; W. Ian Lipkin; Ana I. Negredo; Sergey V. Netesov; Stuart T. Nichol; Gustavo Palacios; Clarence J. Peters; et al. (Archives of Virology, 2010)

Physiological Purkinje Cell Death Is Spatiotemporally Organized in the Developing Mouse Cerebellum - Jakob Jankowski; Andreas Miething; Karl Schilling; Stephan L. Baader (The Cerebellum, 2009)

Effects of the extreme drought in 2003 on soil respiration in a mixed forest - Petia S. Nikolova; Stephan Raspe; Christian P. Andersen; Raphael Mainiero; Helmut Blaschke; Rainer Matyssek; Karl-Heinz Häberle (European Journal of Forest Research, 2009)

Besides Purkinje cells and granule neurons: an appraisal of the cell biology of the interneurons of the cerebellar cortex - Karl Schilling; John Oberdick; Ferdinando Rossi; Stephan L. Baader (Histochemistry and Cell Biology, 2008)

Dynamic causal models of neural system dynamics: current state and future extensions - Klaas E Stephan; Lee M Harrison; Stefan J Kiebel; Olivier David; Will D Penny; Karl J Friston (Journal of Biosciences, 2007)

Channel-induced apoptosis of infected host cells?the case of malaria - Florian Lang; Philipp A. Lang; Karl S. Lang; Verena Brand; Valerie Tanneur; Christophe Duranton; Thomas Wieder; Stephan M. Huber (Pflügers Archiv - European Journal of Physiology, 2004)

Cation channels, cell volume and the death of an erythrocyte - Florian Lang; Karl S. Lang; Thomas Wieder; Svetlana Myssina; Christina Birka; Philipp A. Lang; Stephanie Kaiser; Daniela Kempe; Christophe Duranton; Stephan M. Huber (Pflügers Archiv - European Journal of Physiology, 2003)

Methane and nitrous oxide exchange in differently fertilised grassland in southern Germany - Stephan Glatzel; Karl Stahr (Plant and Soil, 2001)

rRNA based identification and detection systems for rhizobia and other bacteria - Wolfgang Ludwig; Rudolf Amann; Esperanza Martinez-Romero; Wilhelm Schönhuber; Stephan Bauer; Alexander Neef; Karl-Heinz Schleifer (Plant and Soil, 1998)